(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper will describe the way in which UNIFY has successfully integrated multiple technologies, including SimCorp Dimensions, Informatica PowerCenter ETL, Snowflake Cloud-based Data Warehouse, as well as IDL's Data Hub orchestration (or ETL), in order to convert a disparate and fragmented Asset Management platform into a truly cloud-native architecture. Through the use of Phased ETL Strategies and Agile/Scrum governance, UNIFY addresses many of the common challenges associated with legacy systems, including Fragile Integrations, Insufficient Data Sources, and High Maintenance Costs. Additionally, the UNIFY design has standardised data flows, provided for Very High Availability and enabled Seamless Migrations. Performance Studies conducted by the UNIFY development team indicate a marked improvement in overall efficiency, including Significant reductions in Query Costs and Increased Cache Hits; additionally, UNIFY has identified optimization opportunities using its Cost Dashboard. Future efforts will focus on the adoption of advanced technology, including GraphQL Federation, Real-Time Streaming, and AI-Driven Operations, as well as additional opportunities to improve scalability and reduce costs. Overall, the design created by UNIFY establishes a New Industry Standard for IT Transitioning of Asset Management platforms, while ensuring Compliance with Regulatory Requirements and Eliminating Legacy Silos.